Elite athletes` assessment of mental state for competition in individual and team sports - Mladenovic, M. (Sports Science and Health, 2019)
Pre-competition mental state is an important component of a sports outcome. In terms of the type of sport, the results of pre-competition state research differ depending on the methodology used. The aim of this paper was to determine mental states for elite sports competitions in one individual (shooting) and one team sport (handball). The research involved 41 elite athletes of both genders (11 males and 30 females) aged 16 to 34, who were members of the senior national shooting (N1=24) and senior national handball (N2=17) teams of Serbia. The applied instruments included the CSAI-2 and the CA test. Data processing involved descriptive statistics and variance analysis. The results indicate signifi cant differences between athletes in individual and team sport, in favour of team sport athletes. Elite shooters show more cognitive anxiety, they are more prone to mental perception of pain, fear, and reliance on habits and automatism in competitions. Elite handball players showed significantly higher values on scales of desirable mental state for training and competition.